Mixed-method approach on motivational orientations of learning Arabic as a Foreign Language in Malaysia - Ashinida Aladdin (Penerbit Universiti Kebangsaan Malaysia, 2017)
Arabic is always perceived as a language for Muslims specifically Malays in Malaysia because it is a multi-cultural, multi-racial and multi-religion country. The main purpose of this study is to examine the non-Muslim Malaysian learners’ motivational orientations towards learning Arabic as a foreign language in the Malaysian context. A mixed method research approach was adopted in order to answer the research questions in which the instruments of the questionnaire for quantitative data and semi-structured interview were selected for qualitative data collection. The questionnaire was administered to 207 non-Muslim Malaysian learners of Arabic (NMMLAs), while the semi-structured interviews involved 20 respondents. Data from the semi-structured interviews were used to further reinforce the quantitative data collected from the questionnaires, thus providing a deeper understanding and richer representation of the NMMLAs’ orientations for learning Arabic as a foreign language. In determining the underlying orientations toward learning Arabic, the NMMLAs show three types of orientations namely instrumental, intrinsic and integrative. It appears that instrumental orientation is the strongest reason for learning Arabic as the need to fulfil the university requirement. Encouragingly, the NMMLAs show moderate motivation toward both the intrinsic and integrative orientation in learning Arabic. It is hoped that this study provides new insights and perspectives into teaching and learning of the Arabic language to non-Muslim learners in the Malaysian context as well as to offer the teaching of Arabic in a wider context.